2022
DOI: 10.3390/app12020776
|View full text |Cite
|
Sign up to set email alerts
|

How Does the Addition of Biostimulants Affect the Growth, Yield, and Quality Parameters of the Snap Bean (Phaseolus vulgaris L.)? How Is This Reflected in Its Nutritional Value?

Abstract: Recently, the use of biostimulants as natural and eco-friendly fertilizers has received increasing attention because of their efficiency in terms of improving crops’ qualitative and quantitative parameters, i.e., growth, yield, and chemical composition. We studied the effect of four biostimulants—humic acid (20 g/L), vermicompost tea (15 mL/L), moringa leaf extract (1:30 v/v), and yeast extract (5 g/L), with tap water as a control treatment—on the qualitative and quantitative characteristics of snap beans. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 66 publications
3
13
1
Order By: Relevance
“…The results of table (3) indicate that there are moral differences in the addition of organic fertilizer extract to the soil in grain crop values, as the B3 transaction exceeded all transactions by 4.620 mg e -1 . This is consistent with the arrival of [20] when adding three organic fertilizers for two consecutive seasons (Fermbost Tea 15ml -1 , yeast extract 5ml -1 and humomic acid 20gl -1 ) and studying their impact on growth qualities and the yield, which is morally higher than Cambost Tea in the overall outcome compared to the comparison. The results in table (3) show that there are moral differences between the interference between bio-coal and organic fertilizer extract in grain crop values, with the highest A3B3 transaction of 4.896…”
Section: Grain Yieldsupporting
confidence: 76%
“…The results of table (3) indicate that there are moral differences in the addition of organic fertilizer extract to the soil in grain crop values, as the B3 transaction exceeded all transactions by 4.620 mg e -1 . This is consistent with the arrival of [20] when adding three organic fertilizers for two consecutive seasons (Fermbost Tea 15ml -1 , yeast extract 5ml -1 and humomic acid 20gl -1 ) and studying their impact on growth qualities and the yield, which is morally higher than Cambost Tea in the overall outcome compared to the comparison. The results in table (3) show that there are moral differences between the interference between bio-coal and organic fertilizer extract in grain crop values, with the highest A3B3 transaction of 4.896…”
Section: Grain Yieldsupporting
confidence: 76%
“…Fukuji et al [ 12 ] reported higher concentrations of the EAAs Val , Lys , Leu , and Phe and the NEAAs Glu , Pro , and Try in French bean genotypes compared with our data, whereas Asp and Ser were lower. Similarly, El Sheikha et al [ 20 ] reported higher Lys and Arg content and lower Asp and Ser content in pods of French bean variety Polista treated with biostimulants during growth. Moreover, in the study by Nemeskéri [ 26 ], shelled and dry beans had higher concentrations of the EAA Phe and the NEAAs Glu and Tyr , while Asp and Ser were also lower.…”
Section: Resultsmentioning
confidence: 91%
“…Humic acid-enhanced N accumulation and thus improved chlorophyll content in the plant; however, the concentration of the humic substance is the matter (Malik & Azam, 1985;Xu et al, 2012). Also, humic acid application significantly increased the soil plant analysis development (SPAD) reading of the snap bean plant (El Sheikha et al, 2022). In addition, humic acids relieve adjusting plant chlorosis, strengthen plant enzyme systems, and enhance the permeability of the plant membranes (Khaled & Fawy, 2011).…”
Section: Effect Of Humic Acid On Plantmentioning
confidence: 99%
“…The dilution from 1:10 to 1:20 can obtain optimum plant growth (Pant et al, 2012a(Pant et al, , 2012b. The tea and humic acid positively affected plant growth, yield, quality, and nutrition (El Sheikha et al, 2022). Besides, vermicompost tea can be produced by leaching the solution during the composting process, which also contains micronutrients, fulvic acid, and humic acid to improve plant growth (Gutiérrez-Miceli et al, 2008).…”
Section: Spot Of Humic Acidmentioning
confidence: 99%
See 1 more Smart Citation